Mechanical and kinematic alignment in total knee arthroplasty - Schiraldi, Marco (Ann Transl Med, 2016)
In the last 10 years many studies have questioned if the strive to mechanical align any knee may pose some problems related to ligament misbalancing that could explain the high rate of disappointed patients, almost 20% in some reports. Proper indication and difference between patient’s and surgeon’s expectations are among the most important one’s but it must be underlined that, there is indeed a sharp difference between normal knee kinematics, prosthetic knee kinematics and arthritic knee kinematics being the last one extremely variable. A so called kinematic alignment has recently been developed in order to improve patient’s knee function and pain control minimizing any surgical gesture focused on ligaments balance. The amount of bone resections may not affect limb alignment but has an important consequence in ligament tension and balance, clinical result and function therefore a measured bone resection technique is essential in order to perform a proper kinematic alignment. Purpose of this paper is to briefly review the different alignment procedures used for TKA and to discuss their definitions, concepts and evidence on outcome.